LEGALITAS PENYIARAN SIARAN FREE TO AIR MILIK LEMBAGA PENYIARAN SWASTA OLEH LEMBAGA PENYIARAN BERLANGGANAN - Salsabila Amartya (2023)
The limitations of analog TV in broadcasting activities have forced the public to switch to subscription television which is provided by Subscription Broadcasting Institutions which can complement the limitations of ordinary analog TV. In Law no. 32 of 2002 concerning Broadcasting, there is a regulation that requires Subscription Broadcasting Institutions (LPB) to air broadcasts from Private Broadcasting Institutions (LPS). However, this provision intersects with related rights from LPS granted by the state through the Copyright Law. These two provisions have created problems between Broadcasting Institutions. The purpose of this study is to determine the legality of LPB in broadcasting free-to-air broadcasts from LPS and to discuss legal considerations in this matter. The method used is normative juridical with analytical descriptive research. Data collection was carried out by means of a literature study. The results of the study concluded that based on the Copyright Law, LPB was required to have a permit before broadcasting free-to-air broadcasts owned by LPS, whereas the Broadcasting Law did not contain any provisions regarding such licensing. This creates legal uncertainty regarding the free to air broadcasting activities that LPB intends to carry out. Then to solve problems related to broadcasting, it is better to use laws that more specifically regulate broadcasting activities, namely the Broadcasting Law and the Copyright Law. Then the principle of legal benefit in Article 25 of the Copyright Law has not been reflected so that it does not provide benefits to all parties